Healthcare Biotechnology A Practical Guide - Dogramatzis, Dimitris (Taylor & Francis, 2011)
Foreseeing and planning for all of the possibilities and pitfalls involved in bringing a biotechnology innovation from inception to widespread therapeutic use takes strong managerial skills and a solid grounding in biopharmaceutical research and development procedures. Unfortunately there has been a dearth of resources for this aspect of the field.